Influence of light intensity and its spectral composition on photosynthetic activity of cucumber Cucumis sativus under fusarium wilt - Kabashnikova, Luidmila F.; Domanskaya, Irina N.; Pashkevich, Lyubov V.; Dremuk, Irina A.; Martysiuk, Hanna V.; Molchan, Olga V. (Experimental Biology and Biotechnology, 2022)
The responses of cucumber chloroplasts of the Kustovoi variety formed under lighting of different intensity (6000 and 11 000 lx) or under LED lighting with a predominance of red light and far red light to infection with fungus Fusarium oxysporum were studied. The amount of chlorophylls and carotenoids in chloroplasts formed at low light increased in 72 h after infection, and at high light a significant increase in pigment catabolism was observed. Under fusarium wilt, the violaxanthin cycle was not involved in the conditions of the studied light range, and the photochemical activity of chloroplasts did not depend much on the level of illumination. The predominance of red light or far red light caused an increase in both chlorophylls and carotenoids content in terms of the dry mass of the leaf compared to their content in plants grown on white light. Infection on white light and red light caused an increase in the total content of chlorophylls and carotenoids, and a decrease in these parameters relative to healthy plants was noted on far red light. Fusarium wilt led to a decrease in photochemical activity and electron transport of photosystem I (by 20 %) in chloroplasts on red light and far red light. A decrease in the functional efficiency of photosystem II was also observed, most likely due to irreversible changes in pigment-protein complexes with two types of LED lighting. Various mechanisms of the response of cucumber chloroplasts to pathogen infection are discussed, depending on the light conditions of the formation of photosynthetic membranes.
Keywords: chlorophyll; carotenoids; photosystem I; photosystem II; light of different intensity; red light; far red light; Cucumis sativus; Fusarium oxysporum sp.